Overliming effects on xylitol production from sago trunk hydrolysate - Mohamad, Nurul Lina; Mustapa Kamal, Siti Mazlina; Abdullah, Abdul Ghani Liew (Universiti Putra Malaysia Press, 2011)

(untitled)
Xylitol can be obtained from lignocellulosic materials containing xylose. However, the fraction of lignocellulose converted through dilute acid hydrolysis contains compounds that inhibit the fermenting micro-organisms. These inhibitors can be removed from the hydrolysate by detoxification method, prior to fermentation. This study describes effectiveness of overliming process to reduce the toxicity of hydrolysates generated from pre-treatment of sago trunk for xylitol production. The overliming pH 9 and 10 was studied and the results showed that pH 9 was showed 20% of sugar loss, which is low compared to pH 10. Candida tropicalis strain was used to evaluate the fermentability of overlimed sago trunk hydrolysate at pH 9 and non-overlimed hydrolysate medium. Meanwhile, Xylitol accumulation and productivity in the overlimed medium was found to be higher than the non-treated medium. The maximum production of xylitol was increased up to 74% and converted within 76 h. The results obtained improved the fermentation process when compared with the non-treated medium.